Termination of Investigation on Election Crime Cases in 2019 - Arham Syah; Syukri Akub; Audyna Mayasari Muin (LEGAL BRIEF, 2022)
This study aims to analyze what is the basis for stopping the investigation of election crimes and analyze the ideal concept of handling election crimes in Indonesia. The type of research carried out is descriptive analysis, which is a study that intends to provide an overview of something about social phenomena that aims to provide a systematic, factual and accurate description and the discussion in this thesis uses an empirical juridical approach, namely examining existing problems juridically by using laws and regulations. -applicable legislation and legal theories supported by the study of library data. The results of the study show Termination of the investigation of cases of election crimes, based on 2 (two) reasons, namely juridical reasons and non-juridical reasons. The juridical reason is that there is not enough evidence to prosecute, this is based on the provisions of Article 7 paragraph (1) letter i in conjunction with Article 109 paragraph (2) of the Criminal Procedure Code. The non-juridical reason is that in the main case (principal) there has been a Court decision stating Liberation (Vryspraak), while the Election Crime investigated is an assessor (following) on ??the main case. Because the main case has been acquitted, the logical consequence is that the investigation of the election crime case which is assessor in nature must be stopped. 2) The ideal concept in handling election crimes in Indonesia is to strengthen the Bawaslu Institution. The granting of authority to the Bawaslu Institution needs to be carried out, that authority includes the appointment of investigators and public prosecutors. Institutionally, Bawaslu must also be independent in making decisions. Decisions issued are no longer influenced by other institutions.